AVALIAÇÃO DA COMPOSIÇÃO MINERAL DE PÃES ELABORADOS COM TRIGO, AVEIA E SOJA - Kinalski, Tenisa; Schöffer, Jéssie d. N.; Hermanns, Gislaine; Soares, José M.; Fiorentini, Angela M.; Klajn, Vera M. (Salão do Conhecimento, 2013)
Resumo